ANALISIS KINERJA TURBIN ULIR PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DENGAN VARIASI SUDUT KEMIRINGAN POROS - Manotar J Situmorang (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
The screw turbine ( Archimede Screw ) is one type of turbine used in the Micro Hydro Power Plant (PLTMH) system. Archimedes Screw used to be used by humans as a water pump to make it easier to take water from rivers, but over time now the use of Archimedes Screw has turned into a water turbine. Archimedes Screw has the advantage that it is environmentally friendly because it does not interfere with the water ecosystem, has a low head and the resulting efficiency is also quite high. Factors that affect the performance of screw turbines are tilt angle, water head , water flow and bladescrew turbine. The purpose of this research is to find out what is the best slope angle to produce the highest power and efficiency to be applied to Hydroelectric Power Plants (PLTA). Variations in the tilt angle of the screw turbine shaft used in this study were 32º, 37º, 42º and 47º with a blade diameter of 0.35 m, a blade distance of 0.29 m and a blade length of 0.87 m, with a water flow rate of 0.013 m 3 /s. . From the results of this study, the maximum average rotation of the turbine shaft is 194.66 RPM and the generator rotation is 621.33 RPM, the generator power is 36,42 Watt and the highest efficiency is 37,5% at an angle of 47º.